Ancient speciation of the papilionoid legume Luetzelburgia jacana, a newly discovered species in an inter‐Andean seasonally dry valley of Colombia. Issue 5 (3rd September 2018) - da Cruz, Daiane Trabuco; Idárraga, Álvaro; Banda, Karina; Cogollo, Álvaro; van den Berg, Cássio; de Queiroz, Luciano Paganucci; Pennington, R. Toby; Lavin, Matt; Cardoso, Domingos Benício Oliveira Silva
Abstract: Ecology, geography, morphology, and a combined phylogenetic analysis of DNA sequence variation support the recognition of the new species Luetzelburgia jacana (Leguminosae, Papilionoideae, vataireoid clade). This species is found in the inter‐Andean Rio Cauca Valley in Colombia. Phylogenetic analyses of nine plastid and nuclear DNA sequences from 44 accessions representing all known Luetzelburgia species show that L. jacana is sister to the rest of the genus and has a mean estimated stem age of ca. 4 Ma, much older than other Luetzelburgia species. Luetzelburgia jacana is distinguished by a combination of mostly 7–9‐foliolate, glabrous leaves with leaflets obtuse to shortly acute at the apex, flowers up to 9.6 mm long, and samaras bearing two small lateral wings on the seed chamber. Luetzelburgia jacana, along with two other earliest‐branching species in the genus, L. guaissara and L. trialata, are geographical outliers in the genus, with L. jacana having the northernmost distribution and L. guaissara and L. trialata having the southernmost distributions. These three earliest‐branching species are also ecological outliers within Luetzelburgia by occurring in wetter and less seasonal settings than other species. The discovery of L. jacana resolves these three earliest‐branching species in Luetzelburgia as ecologically transitional between most species of the vataireoid clade that inhabit wet forests and most species of Luetzelburgia that inhabit highly seasonal dry forests and woodlands.